Importance of adverse drug reaction reporting in dental practice - Dorota Ochyra; Bartłomiej Ochyra; Zofia Misztal; Marta Pawlicka; Mateusz Pawlicki; Anna Mroczek; Kamil Bałabuszek (Kazimierz Wielki University, 2018)
Dentists in their daily practice could observe adverse drug reactions (ADR) in specific location and after specific medicinal products. As a dentist practitioner it is very important to be aware of what ADR is, what we can do to manage it and what it brings to everyday practice. The level of adverse drug reaction reporting by healthcare professionals (HCPs) is definitely unsatisfactory. One of the most important reasons of this situation is low knowledge about ADRs reporting rules, especially among students and young HCPs. This situation can be changed through increasing the number of hours devoted to this issue during studies. Highlighting the importance of ADRs reporting, even one serious individual case safety reports (ICSRs), in the context of signal detection is necessary.